Riociguat treatment for portopulmonary hypertension: a subgroup analysis from the PATENT-1/-2 studies. (May 2018) - Cartin-Ceba, Rodrigo; Halank, Michael; Ghofrani, Hossein-Ardeschir; Humbert, Marc; Mattson, John; Fritsch, Arno; Krowka, Michael
In patients with portopulmonary hypertension (n = 13) included in the 12-week randomized placebo-controlled PATENT-1 trial, riociguat was well tolerated and improved 6-min walking distance (6MWD), World Health Organization functional class (WHO FC), and other efficacy parameters; 6MWD and WHO FC improvements were sustained over two years in the open-label extension, PATENT-2.